The Sex Specific Association Between Maternal Gestational Diabetes and Offspring Metabolic Status at 1 Year of Age - Du, Qinwen; Sompolinsky, Yishai; Walfisch, Asnat; Zhong, Huiping; Liu, Yan; Feng, Weiwei (Frontiers in Endocrinology, 2021)
Previous studies showed the association between maternal GDM and long-term effects of overweight in offspring. However, the nature of this association in the early postnatal period is still undetermined. The aim of this prospective cohort study was to evaluate whether maternal GDM is associated with overweight and obesity status in offspring at age 1 year. We studied 1167 infants born at a large obstetrical care hospital including 778 normal glucose tolerance (NGT) and 389 GDM pregnancies, matched in a 1:2 ratio according to offspring’s gender, during the years 2016-2017. Overweight and obesity status in offspring of both groups were evaluated at 1 year of age through questionnaires. Infant outcomes were defined according to the WHO Child Growth Standards based on the length-based BMI-for-age. Female offspring from the GDM group exhibited a higher mean BMI (17.2 vs. 16.6, p < 0.01), a higher rate of obesity (13.9% vs. 7.7%; p < 0.05), and overweight (33.1% vs. 23.5%; p < 0.05) as compared to the NGT female group. In the multivariable regression model, maternal GDM was found to be independently and significantly associated with overweight or obesity in 1-year aged female offspring only (OR 1.61, 95% CI 1.09–2.37, p < 0.05). We found a sex specific association between maternal GDM and the overweight risk only in female offspring at 1 year of age.